Model Pembelajaran Problem Based Learning Berbantuan Media Kahoot dalam Meningkatkan Hasil Belajar Fisika - Saputra, Dodi; Hasyim, Mutahharah; Anwar, Anwar; Sulaeman, Sulaeman (Universitas Negeri Makassar, 2024)
Abstract. The purpose of this study was to determine the increase in physics learning outcomes of students in class XII-IPA 4 SMA Negeri 2 Bantaeng on dynamic electrical (Direct Current) material by using a learning model Problem Based Learning with the help of kahoot media. The type of research used this time is collaborative classroom action research (PTK) which consists of 2 cycles. The research subjects were 31 students of class XII IPA 4. Data collection is through teacher observation and giving tests at the end of each cycle. Based on the results of this research, the average value of student learning outcomes was 60.97 in cycle 1 and 81.48 in cycle 2. Classical mastery of learning outcomes reached 48.39% in cycle 1 and 87.10% in cycle 2. So the conclusion in this research is there is an increase in the percentage of completeness of learning outcomes by 38.71%. Keywords: Kahoot Media, Physics Learning Outcomes, Problem Based Learning